A novel serine racemase inhibitor suppresses neuronal over-activation in vivo. Issue 14 (15th July 2017) - Mori, Hisashi; Wada, Ryogo; Takahara, Satoyuki; Horino, Yoshikazu; Izumi, Hironori; Ishimoto, Tetsuya; Yoshida, Tomoyuki; Mizuguchi, Mineyuki; Obita, Takayuki; Gouda, Hiroaki; Hirono, Shuichi; Toyooka, Naoki
Graphical abstract: Abstract: Serine racemase (SRR) is an enzyme that producesd -serine froml -serine.d -Serine acts as an endogenous coagonist of NMDA-type glutamate receptors (NMDARs), which regulate many physiological functions. Over-activation of NMDARs induces excitotoxicity, which is observed in many neurodegenerative disorders and epilepsy states. In our previous works on the generation of SRR gene knockout (Srr-KO) mice and its protective effects against NMDA- and Aβ peptide-induced neurodegeneration, we hypothesized that the regulation of NMDARs' over-activation by inhibition of SRR activity is one such therapeutic strategy to combat these disease states. In the previous study, we performed in silico screening to identify four compounds with inhibitory activities against recombinant SRR. Here, we synthesized 21 derivatives of candidate1, one of four hit compounds, and performed screening by in vitro evaluations. The derivative13J showed a significantly lower IC50 value in vitro, and suppressed neuronal over-activation in vivo .